Identification of two major autoantigens negatively regulating endothelial activation in Takayasu arteritis - Mutoh, Tomoyuki (Nat Commun, 2020)
The presence of antiendothelial cell antibodies (AECAs) has been documented in Takayasu arteritis (TAK), a chronic granulomatous vasculitis. Here, we identify cell-surface autoantigens using an expression cloning system. A cDNA library of endothelial cells is retrovirally transfected into a rat myeloma cell line from which AECA-positive clones are sorted with flow cytometry. Four distinct AECA-positive clones are isolated, and endothelial protein C receptor (EPCR) and scavenger receptor class B type 1 (SR-BI) are identified as endothelial autoantigens. Autoantibodies against EPCR and SR-BI are detected in 34.6% and 36.5% of cases, respectively, with minimal overlap (3.8%). Autoantibodies against EPCR are also detected in ulcerative colitis, the frequent comorbidity of TAK. In mechanistic studies, EPCR and SR-BI function as negative regulators of endothelial activation. EPCR has also an effect on human T cells and impair Th17 differentiation. Autoantibodies against EPCR and SR-BI block the functions of their targets, thereby promoting pro-inflammatory phenotype.